Pendidikan dan Pelatihan Kesehatan Penyusunan Food Record dan Manajemen Nutrisi pada Pendertia atau Keluarga Penderita Diabetes Mellitus di Desa Sukahurip - Setiyono, Andik; Laferani, Yuni (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
In 2021, an estimated 537 million people worldwide suffered from diabetes mellitus. This number is expected to continue to rise annually until 2045, when it is estimated that diabetes sufferers will reach 785 million people, or 1 in 8 adults. Type 2 diabetes mellitus is a chronic disease characterized by elevated blood sugar levels in the body due to insulin resistance or inadequate insulin production. The purpose of community service is to improve the knowledge and skills of sufferers or their families in filling out and calculating food records to support effective nutritional management in the prevention and control of diabetes mellitus. The method is carried out through providing health education and training on compiling food records targeting sufferers or their families with diabetes mellitus in Sukahurip Village. The results of this community service were tested using statistical tests with a dependent T-test obtained p-value = 0.001, meaning that statistically there is a significant difference in knowledge between before and after the provision of health education and training. Health education and training have been proven effective in improving knowledge and skills.